Safety of Onabotulinumtoxin-A for Chronic Migraine During Pregnancy and Breastfeeding: A Narrative Review - Antonio Russo; Luigi Francesco Iannone; Ilaria Orologio; Veronica Rivi; Alberto Boccalini; Flavia Lo Castro; Marcello Silvestro; Simona Guerzoni (Toxins)
Onabotulinumtoxin-A (onabotA) is a neurotoxin widely used for several indications, including chronic migraine (CM) preventive treatment, due to its well-demonstrated efficacy, tolerability, and safety. However, onabotA safety during pregnancy and breastfeeding remains unclear, as these populations are typically excluded from clinical trials. The action of onabotA starts locally at the injection sites, modulating the pain pathway with minimal systemic absorption, which theoretically minimizes risks to the fetus or breastfeeding infant. Preclinical studies demonstrate that onabotA does not distribute systemically in significant amounts after administration, although adverse fetal outcomes in rats and rabbits were reported when injected at high doses. Limited human data suggest that onabotA exposure during pregnancy may not be associated with major malformations or significant adverse outcomes for the fetus, especially when used at therapeutic doses for migraine prevention during the first trimester or earlier. Data on breastfeeding are even scarcer but indicate a low likelihood of drug transfer into breast milk. This narrative review highlights the available evidence on the use of onabotA in pregnancy and breastfeeding women, including real-word evidence, with a focus on the use for CM.